The Role of Relationship Marketing on Student Loyalty in Using Marketplace Applications - Noviadry Nur Tamtama; Rahmawati Riantisari (LPPM Universitas Buddhi Dharma, 2024)
The development of e-commerce in Indonesia is increasingly rapid. This development has an impact on very tight competition not only in almost all industries in the Indonesian economy, including the Micro, Small and Medium Enterprises (MSME) sector which sells products or services online, but also competition between companies providing marketplace platforms or applications. . The aim of this research is to assess the impact of customer satisfaction and increasing customer satisfaction on loyalty. This research is quantitative. Sampling was based on certain criteria, namely students in Yogyakarta who used marketplace applications. The sample size was taken using the Cochran formula. So a sample of 350 students was obtained. Data collection through questionnaires accommodated via Google Form. The data that has been collected is then subjected to initial testing, namely validity, reliability, basic assumption test and classical assumption test. After the data is deemed appropriate, the research hypothesis is then tested using a multiple regression test. The result is that customer satisfaction influences student loyalty in using marketplace applications by looking at a significance value of less than 0.05. Increasing customer satisfaction influences student loyalty in using the Marketpalace application as evidenced by a significance value of less than 0.05. The coefficient of determination test result is 0.566, meaning that customer satisfaction and increasing customer satisfaction can have an impact on loyalty of 56.6%. The researcher's suggestion for further research is to look for other variables that have a big influence on loyalty.